1998
DOI: 10.1111/j.1469-7793.1998.655ba.x
|View full text |Cite
|
Sign up to set email alerts
|

Two mutations linked to nocturnal frontal lobe epilepsy cause use‐dependent potentiation of the nicotinic ACh response

Abstract: Two mutations in the M2 region of the human á4 neuronal nicotinic subunit -á4(S248F) and á4(776ins3) -have been linked to autosomal dominant nocturnal frontal lobe epilepsy (ADNFLE) (Steinlein et al. 1995(Steinlein et al. , 1997. The á4(S248F) mutation is a serine to phenylalanine substitution at position 248 in the human á4 nicotinic subunit. The á4(776ins3) mutation is a 3-base pair insertion that adds a leucine at position 259 in the amino acid sequence of the human á4 subunit. Photo-affinity labelling and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
65
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 33 publications
14
65
3
Order By: Relevance
“…First, current amplitudes were measured in a large number of cells . At variance with previous reports performed in "homozygous" conditions (Weiland et al, 1996;Kuryatov et al, 1997;Steinlein et al, 1997;Figl et al, 1998), no significant variation in the maximal AChevoked currents could be observed in control versus ADNFLE conditions. Second, determination of the receptor sensitivity, over a broad range of agonist concentrations, revealed that all mutant nAChRs displayed an increased ACh sensitivity with respect to wild-type receptors (Bertrand et al, , 2002Moulard et al, 2001).…”
Section: Mutations and Functional Properties Of Nicotinic Receptors Acontrasting
confidence: 54%
“…First, current amplitudes were measured in a large number of cells . At variance with previous reports performed in "homozygous" conditions (Weiland et al, 1996;Kuryatov et al, 1997;Steinlein et al, 1997;Figl et al, 1998), no significant variation in the maximal AChevoked currents could be observed in control versus ADNFLE conditions. Second, determination of the receptor sensitivity, over a broad range of agonist concentrations, revealed that all mutant nAChRs displayed an increased ACh sensitivity with respect to wild-type receptors (Bertrand et al, , 2002Moulard et al, 2001).…”
Section: Mutations and Functional Properties Of Nicotinic Receptors Acontrasting
confidence: 54%
“…Although the functional abnormalities of both mutant nAChR with S280F and insL are loss-of-function (enhanced steady-state desensitization) with gain-of-function (enhanced ACh sensitivity and use-dependent potentiation) [41][42][43], both knock-in mice; pS280F-KM and insL-KM, are considerably more sensitive to nicotine-induced seizures than wild-type mice. Indeed, in nicotine-induced seizure tests, these two types of knock-in mice show a lower threshold dose of nicotine for generalized seizures, shorter latencies to seizure onset, and longer seizure durations compared with their wild-type littermates [8].…”
Section: Predictive Validity Of Adnfle Modelsmentioning
confidence: 99%
“…We used an ACh concentration (2 M) near the previously reported rat WT and ␣4(S252F)␤2 EC 50 for ACh (Kuryatov et al, 1997;Figl et al, 1998) and a mecamylamine concentration (0.5 M) near the range of IC 50 values previously reported for human ␣4␤2-nAChRs (Papke et al, 2001). As reported previously (Weiland et al, 1996;Kuryatov et al, 1997;Bertrand et al, 1998;Figl et al, 1998), the ␣4(S252F) mutation enhanced agonist-induced desensitization. Successive applications of 2 M ACh at 3 min intervals had no significant effect on the peak WT response but reduced the peak mutant response significantly ( p Ͻ 0.05) (Fig.…”
Section: The Dac Is Not Associated With Epileptiform Changes On Epidumentioning
confidence: 99%